I died for beauty : Dorothy Wrinch and the cultures of science - Senechal, Marjorie (Oxford University Press, 2013)
"In the vein of A Beautiful Mind, The Man Who Loved Only Numbers, and Rosalind Franklin: The Dark Lady of DNA, this volume tells the poignant story of the brilliant, colorful, controversial mathematician named Dorothy Wrinch. Drawing on her own personal and professional relationship with Wrinch and archives in the United States, Canada, and England, Marjorie Senechal explores the life and work of this provocative, scintillating mind. Senechal portrays a woman who was learned, restless, imperious, exacting, critical, witty, and kind. A young disciple of Bertrand Russell while at Cambridge, the first women to receive a doctor of science degree from Oxford University, Wrinch's contributions to mathematical physics, philosophy, probability theory, genetics, protein structure, and crystallography were anything but inconsequential. But Wrinch, a complicated and ultimately tragic figure, is remembered today for her much publicized feud with Linus Pauling over the molecular architecture of proteins. Pauling ultimately won that bitter battle. Yet, Senechal reminds us, some of the giants of mid-century science--including Niels Bohr, Irving Langmuir, D'Arcy Thompson, Harold Urey, and David Harker--took Wrinch's side in the feud. What accounts for her vast if now-forgotten influence? What did these renowned thinkers, in such different fields, hope her model might explain? Senechal presents a sympathetic portrait of the life and work of a luminous but tragically flawed character. At the same time, she illuminates the subtler prejudices Wrinch faced as a feisty woman, profound culture clashes between scientific disciplines, ever-changing notions of symmetry and pattern in science, and the puzzling roles of beauty and truth"--